Коли місто Козелець отримало маґдебурзьке право? - Арістов, В. (Український історичний журнал, 2021)
Дата й обставини отримання Козельцем маґдебурзького права досі були предметом дискусії. Суперечки спиралися на два документи: універсал гетьмана Б.Хмельницького 1656 р. про звільнення козелецьких міщан від низки повинностей і привілей короля Яна
Казимира 1663 р. Проте головний документ – перша жалувана грамота – не був відомий
у науці й залишався неопублікованим. Стаття заповнює цю археографічну лакуну. У фондах Національного музею історії України зберігається грамота царя Олексія Михайловича
1655 р., який надав міщанам Козельця маґдебурзьке право. Текст акта, а також супровідного аркушу, що був доданий після 1667 р., публікується у цій статті, що дозволяє відновити
історію отримання Козельцем міських прав. Другим відомим документом козелецького самоврядування став універсал Б.Хмельницького 1656 р. Улітку 1663 р. недоторканність прав
міщан підтвердив гетьман І.Брюховецький. Невдовзі грамота Олексія Михайловича була
вивезена з Козельця королем Яном Казимиром під час походу на Лівобережжя України в
1663–1664 рр. Натомість він видав новий привілей від власного імені. На прикладі документів 1655–1663 рр., пов’язаних з утвердженням у Козельці маґдебурзького права, можна
простежити, як формувалися міські перекази про «давні права». Верхівка міщан Козельця
на чолі з О.Долинським швидко «винайшла» традицію про те, що «права і свободи» надали місту «давні» польські королі. За іронією долі, справжнє надання привілею польським королем поклало кінець цій традиції. The date and circumstances of Kozelets’s acquisition of Magdeburg law have so far been
the subject of debate. Disputes over the introduction of Magdeburg law in Kozelets were based
on two documents: the universal of Hetman B.Khmelnytskyi (1656) on the release of Kozelets
citizens from a number of duties and the letters patent of King John Casimir (1663). However,
the main document – the first letters patent – was not known in the scholarship and remained
unpublished. The article fills this archeographic gap. The funds of the National Museum of
Ukrainian History contain a diploma of Tsar Oleksiy Mykhailovych of 1655, who granted the
townspeople of Kozelets the Magdeburg law. The text of the diploma, as well as the accompanying
sheet, which was added after 1667, is published in this article. Taking into account this document
it is possible to reconstruct the history of how Kozelets obtained city rights. In 1655 the citizens
submitted a petition to the tsar for a letters patent. Their request was granted and a diploma was
issued, which is now in the National Museum of the History of Ukraine. It is probable that the
petition of the citizens to the Tsar was caused by the activity of I.Vyhovskyi, who in 1654 received
from Aleksey Mikhailovich the right to possession of a number of villages, towns and cities. One
of them was Kozelets. The second known document in the history of Kozelets self-government
was the universal of Hetman B.Khmelnytskyi (1656). In the summer of 1663, the inviolability of
the rights of the citizens of Kozelets was confirmed by Hetman I.Briukhovetskyi. Soon Aleksey
Mikhailovich’s diploma was taken out of Kozelets by the King John Casimir during the campaign
to the Left-Bank Ukraine in 1663–1664. Instead, the king issued a new letters patent on his own
behalf. On the example of the documents of 1655–1663, connected to the establishment of
Magdeburg law in Kozelets, it is possible to trace how the city legends about “old rights” were
formed. The top citizens of Kozelets, led by O.Dolynskyi, quickly “invented” the tradition about
the “rights and freedoms” given to the city by “old” Polish kings. Ironically, the real granting of the
letters patent by the Polish king put an end to this tradition.